(3GdajV GdeOjO aj CNHGQ Gdfjd GdSYjOs - (3CHh GdYHGS CMeO Hf eMeO Gdefhai GdTGaYjs; (3eMeO GdeZQHjs
(3ChdgG (B:s
(3hHYO aEf Gddg JYGdi HdWja MceJg GdXGgQI LYd Gdfjd GdeHGQc ef BjGJg s
(3BNQgG (B:s
(3aGSJLGH Gddg JYGdi dgPg GdCeI ceG GSJLGH dfHjg ehSi Ydjg GdUdGI hGdSdGe s
(3HgG fXcGe GdJYbjHIs
(3LeYg ef GdLRA GdKGdK ef cJGH GdQhV GdfVjQs
(3fSNI KGfjI s
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdLZQGajG h GdHdOGfs